Le stage dans l’enseignement supérieur, un dispositif riche de promesses difficiles à tenir - Dominique Glaymann (Éducation et Socialisation)
Internships are part of a pedagogical system which is attracting more and more interest in Academia. This phenomenon may be explained by the fact that it would seem that they encourage the professionalization of studies and facilitate improved professional insertion of young graduates. This article falls in line with a research-work logic which has been led since 2006 in order to gain better understanding of the reality of internships, putting together sets of recommendations in order to improve their function. After having demonstrated the limits of the efficiency of internships in terms of a response to graduates’ insertion difficulties which are linked to the employment system as opposed to the educational system, the present work describes the potential input of these internships from the point of view of education, socialization and professionalization. The paper is further concerned by the conditions that should be brought together so that a « good » internship may materialize these possibilities while warning against the major risks that the current inflation of internships is generating.